A Serial-Parallel FDTD Approach for Modeling the Coupling problem between Two Large Arrays - Mittra, Raj; Huang, Neng-Tien; Raouf, Hany E. Abd-El- (Applied Computational Electromagnetics Society Journal (ACES), 2022)
Solution of large problems using a numerically rigorous approach is always challenging because of the heavy burden they impose on the CPU. In this paper we introduce a new serial-parallel FDTD approach to solve large electromagnetic problems, e.g., coupling between two arrays separated by a large distance, that is difficult to handle via a direct application of the FDTD algorithm because of large size. This technique is based on dividing the original problem into relatively small sub-regions, and evaluating the solution that are localized in each of these sub-regions. The excitation of the sub-regions can either be direct sources, as for instance in the aggressor array, or be derived from the fields propagating into domain–from adjacent regions through the interfaces. We show that the results obtained by using the proposed approach compare well with the direct FDTD solution for some test problems, involving coupling between two phased arrays. Of course, the advantage of using the serial-parallel approach is that it can handle very large problems, well beyond the scope of the direct methods.